Bacteriological study of upper respiratory tract infection in pediatric patients - Shrestha, A; Sherchand, JB; Sharma, PR; Bhatta, DR (Journal of Institute of Medicine Nepal, 2007)
Background: The study was conducted with aims to identify the causative bacterial agents of upper respiratory tract infection ( URTI ) among pediatric patients and to reveal the antibiotic susceptibility pattern of the major pathogen during November 2001 to October 2002. Methods: The throat swab samples from 192 children suspected of URTI were obtained from the outpatient department of Kanti Children’s Hospital and inoculated in the culture medium. The bacterial infection was confirmed only in 152 patients. The organisms isolated on medium were identified by their cultural, morphological and biochemical characteristics. Results: The infections were found to be due to S. pyogenes, S. aureus and S. pneumoniae. Most of the infections were due to S. pyogenes. The information obtained during sample collection showed that the high rate of infection was found to be in male patients, in infants and in urban children. Antibiotic susceptibility pattern for the isolated organisms revealed that Amoxycillin and Cephalexin, Erythromycin and Cephalexin were the most effective for S. pyogenes and S. aureus respectively whereas both Amoxycillin and Cephalexin were equally and the most effective for S. pneumoniae. The effective antibiotic for overall URTI was found to be Amoxycillin Conclusion: The study concluded that despite the existence of so many pathogens, and the susceptible antibiotics, Amoxycillin has been found to be the most effective against the pathogens causing URTI among pediatric population. Key words: antibiotic, susceptible, resistant, acute respiratory infection The full text of this paper is available at Journal of Institute of Medicine website